Empowering MSMEs: The Role of Fintech, Financial Literacy, and Self-Efficacy in Financial Management in Tanjung Raja - Vivit Pelantri; Fitriasuri (LP2M IAIN Palopo, 2025)
This study investigates the influence of financial technology, financial literacy, and financial self-efficacy on the financial management practices of MSME actors in Tanjung Raja District. Employing a descriptive quantitative approach, the research utilises primary data collected through live questionnaires distributed to 85 respondents. The analysis was conducted using multiple linear regression, with all variables measured using a Likert scale. The findings reveal that both financial technology and financial literacy have a significant positive impact on the financial management of MSMEs. Conversely, financial self-efficacy does not show a significant effect. These results highlight the importance of technological adoption and financial knowledge in enhancing MSME financial decision-making, while suggesting that self-efficacy alone may not be sufficient without supporting resources and skills.